Sub-Inhibitory Concentrations of Chlorhexidine Induce Resistance to Chlorhexidine and Decrease Antibiotic Susceptibility in Neisseria gonorrhoeae - Laumen, Jolein G. E.; Van Dijck, Christophe; Manoharan-Basil, Sheeba S.; Abdellati, Saïd; De Baetselier, Irith; Cuylaerts, Vicky; De Block, Tessa; Van den Bossche, Dorien; Xavier, Basil B.; Malhotra-Kumar, Surbhi; Kenyon, Chris (Frontiers in Microbiology, 2021)
Objectives Chlorhexidine digluconate (chlorhexidine) and Listerine mouthwashes are being promoted as alternative treatment options to prevent the emergence of antimicrobial resistance in Neisseria gonorrhoeae. We performed in vitro challenge experiments to assess induction and evolution of resistance to these two mouthwashes and potential cross-resistance to other antimicrobials. Methods A customized morbidostat was used to subject N. gonorrhoeae reference strain WHO-F to dynamically sustained Listerine or chlorhexidine pressure for 18 days and 40 days, respectively. Cultures were sampled twice a week and minimal inhibitory concentrations (MICs) of Listerine, chlorhexidine, ceftriaxone, ciprofloxacin, cefixime and azithromycin were determined using the agar dilution method. Isolates with an increased MIC for Listerine or chlorhexidine were subjected to whole genome sequencing to track the evolution of resistance. Results We were unable to increase MICs for Listerine. Three out of five cultures developed a 10-fold increase in chlorhexidine MIC within 40 days compared to baseline (from 2 to 20 mg/L). Increases in chlorhexidine MIC were positively associated with increases in the MICs of azithromycin and ciprofloxacin. Low-to-higher-level chlorhexidine resistance (2-20 mg/L) was associated with mutations in NorM. Higher-level resistance (20 mg/L) was temporally associated with mutations upstream of the MtrCDE efflux pump repressor (mtrR) and the mlaA gene, part of the maintenance of lipid asymmetry (Mla) system. Conclusions Exposure to sub-lethal chlorhexidine concentrations may not only enhance resistance to chlorhexidine itself but also cross-resistance to other antibiotics in N. gonorrhoeae. This raises concern regarding the widespread use of chlorhexidine as an oral antiseptic, for example in the field of dentistry.